1999
DOI: 10.1088/0953-8984/11/36/313
|View full text |Cite
|
Sign up to set email alerts
|

Metamagnetic transition and magnetocaloric effect in ErCo2

Abstract: The magnetization MH(T) and the specific heat capacity cP,H(T) of the ErCo2 intermetallic compound were measured in the temperature range 5 - 100 K and in 0, 7 or 14 T applied field, respectively. A clear first-order phase transition is found at the magnetic ordering of the Er sublattice. While for order-disorder transitions in simple ferromagnets there is a good agreement between magnetocaloric performance predicted on the basis of magnetization measurements compared to calorimetric measurements, it is necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
51
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 23 publications
4
51
0
4
Order By: Relevance
“…13,14 Moreover, the large entropy change showed by ErCo 2 has led to studies on the MCE properties of the pure and pseudobinary Co Laves phases. 2,[15][16][17][18][19][20][21][22] We have also selected the ferromagnetic manganites, La 2/3 ͑Ca x Sr ͑1−x͒ ͒ 1/3 MnO 3 with x = 0, 0.5, and 1, in order to give more generality to our results. The physical properties of these materials have been reported in literature.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Moreover, the large entropy change showed by ErCo 2 has led to studies on the MCE properties of the pure and pseudobinary Co Laves phases. 2,[15][16][17][18][19][20][21][22] We have also selected the ferromagnetic manganites, La 2/3 ͑Ca x Sr ͑1−x͒ ͒ 1/3 MnO 3 with x = 0, 0.5, and 1, in order to give more generality to our results. The physical properties of these materials have been reported in literature.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In particular, the study of the Co band has been the subject of intense investigation for decades. [5][6][7][8][9][10][11][12][13] In these compounds, the Co sublattice is near the critical condition for the formation of magnetic moment, turning the Co 3d-electron system very sensitive to the internal field created by the R sublattice or to changes of external parameters. Particularly unique is the case of the Co sublattice in ErCo 2 , as it is just above the condition for undergoing a metamagnetic transition.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly unique is the case of the Co sublattice in ErCo 2 , as it is just above the condition for undergoing a metamagnetic transition. 1,7,14,15 The ErCo 2 structure is cubic above the first-order ferrimagnetic ordering transition (T c = 32 K at H = 0 T), which has an associated rhombohedral distortion of the crystal structure. 16 The magnetic behavior of the compound is mostly dominated by the Er sublattice at all temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that MCE properties of HoCo 2 and ErCo 2 were investigated. According to Tishin et al [10] for HoCo 2 the maximum T ad at 84 K reaches 10 K for a field change µ 0 H of 10 T. Giguere et al [11] reported the maximum T ad = 14.4 K for ErCo 2 at 33 K for µ 0 H = 14 T. In the case of Ho 1 − x Er x Co 2 some theoretical calculation was performed by Oliveira et al [12]. They have shown that the introduction of Er ions decreases the magnetic ordering temperature of the pseudobinary compounds and the nature of the magnetic phase transitions continues to be first-order for all Er concentrations.…”
Section: Introductionmentioning
confidence: 97%